Deposition of graphene and related nanomaterials by dynamic spray-gun method: a new route to implement nanomaterials in real applications. (31st May 2019) - Bondavalli, Paolo; Pribat, Didier; Legagneux, Pierre; Martin, Marie-Blandine; Hamidouche, Louiza; Qassym, Lilia; Feugnet, Gilles; Trompeta, Aikaterini-Flora; Charitidis, Constantinos A
Abstract: The dynamic spray-gun deposition method was developed in 2006 to fabricate field effect transistors based on random arrays of carbon nanotubes (CNTs) field effect transistors for gas sensing applications. Thanks to this deposition method, we were able to fabricate hundreds of operational devices in a reproducible way that were integrated in electronic chips. Following this first implementation, we decided to widen the application of the deposition technique to the field of Energy and specifically to the fabrication of supercapacitors. In this context, we demonstrated in 2012 the fabrication of nanostructured electrodes for supercapacitors, using mixtures of graphene/graphite and CNTs increasing the device capacitance and the power delivered of a factor 2.5 compared to CNT based electrochemical-double-layer-capacitors. Indeed, with high quality graphene we could reach a value of around 100 W Kg −1 . This value is extremely promising also considering that it has been obtained with an industrially suitable technique. This dynamic spray-gun deposition has been also exploited for the fabrication of resistance based random access memories, making use of thin layers of graphene oxide and of oxidized carbon nanofibers. In the first case, 5000 cycles of 'write' and 'read' phases were demonstrated. These results pave the way for the fabrication of very low cost memories that can be embedded in smart-cards, patches for health monitoring (e.g. diabetes), ID cards, RFID tags and more generally smart packaging. Finally we are also working on the utilization of this technique for the fabrication of layers for electro-magnetic interference shielding application. Thanks to a new machine with four nozzles, developed within the frame of the Graphene Flagship project, we are able to deposit four different nanomaterials at the same time or alternatively on a large surface (30 cm × 30 cm) creating specific nano-structuration and therefore ad hoc architectures allowing the smart absorption of specific frequencies (e.g. X-band). All these applications demonstrate the extreme versatility of this technique that constitutes a real breakthrough for exploiting the nanomaterials characteristics in real devices, using an industrial suitable fabrication method that can be implemented using roll-to-roll technique.